Institucionalização da educação híbrida: um estudo sobre o uso de tecnologias digitais em instituições públicas de ensino superior - Mauricio, Gustavo Carvalho (Universidade Federal de São Carlos, 2024)
This research aims to analyze the institutionalization of Hybrid Education, focusing on the incorporation of Digital Information and Communication Technologies (DICT) in face-to-face courses within public higher education institutions. It considers technical, communicational, normative, and pedagogical aspects. Data analysis was conducted with the support of the Parsif.al tool, whose methodology facilitated the extraction and synthesis of information. The research is based on a Systematic Literature Review, using the SciELO, Capes Journals, and Web of Science databases to map and analyze articles published between 2003 and 2023. The review addresses technical, communicational, normative, and pedagogical aspects involved in the implementation of Distance Education and Hybrid Education, aiming to systematize the knowledge already disseminated on the subject. The methodological process included selecting studies based on strict criteria, such as the presence of descriptors in the title, abstract, or keywords, resulting in the inclusion of 46 relevant articles. Additionally, the Institutional Development Plans of ten Brazilian Public Higher Education Institutions were analyzed, observing various scenarios related to DICT implementation and integration strategies. The research suggests that, to achieve an effective integration of Hybrid Education in these institutions, it is essential to invest in well-defined institutional policies, ensure continuous technical support, and adapt pedagogical practices to meet the needs and challenges of the current educational context. These elements are essential for fostering a dynamic teaching and learning experience aligned with the demands of an increasingly digital society.
Institutionalization of hybrid education: a study on the integration of digital technologies in on-campus courses at public higher education institutions
Keywords: Educação híbrida; TDIC; Institucionalização; Educação a distância; Hybrid education; DTIC; Institutionalization; Distance education; CIENCIAS HUMANAS::EDUCACAO